Title Page & Editorial Page (International Journal of Pathology, 2022)
Patron: Anwar Ul HaqueChief Editor: Nuzhat S. Khattak Managing Editor: Waheed Iqbal Associate Editor: Feroz AliAssistant Editor: Rehmat Khan Imran NazirMembers Editorial Board International: Shakeel Faisal (USA)Thomas Helland (Norway)Xingyuan Yang (China)Waqas Sami (Saudi Arabia)Deema Hussein (Jeddah) Hazrat Bilal (China)Members Editorial Board National: Ahmareen Khalid (Islamabad) Sadaf Durrani (Peshawar) Irfan Ullah (Lahore)Romana Idress (Karachi)